2019
DOI: 10.2174/1381612825666190618121553
|View full text |Cite
|
Sign up to set email alerts
|

Recent Advances in Solid Dispersion Technology for Efficient Delivery of Poorly Water-Soluble Drugs

Abstract: Drug discovery is generally considered as a costly affair and it takes approximately 15 years to reach a new chemical entity into the market. Among the recent potent drug molecules with most effective pharmacological properties, very few reached for Phase I clinical trial in humans. Unfortunately, the historical average reveals an almost 90% overall attrition rate in clinical trials. The solubility and permeability of a drug are the critical factors influencing the success of a drug. Oral drug delivery systems… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(20 citation statements)
references
References 86 publications
0
20
0
Order By: Relevance
“…The term SD has been defined as a dispersion of one or more active moiety in a suitable inert carrier or matrix in a solidstate. It can be prepared by different formulation methodologies (Paudwal et al, 2019). The drug molecule can be dispersed in a different form to prepare the SDs.…”
Section: Introductionmentioning
confidence: 99%
“…The term SD has been defined as a dispersion of one or more active moiety in a suitable inert carrier or matrix in a solidstate. It can be prepared by different formulation methodologies (Paudwal et al, 2019). The drug molecule can be dispersed in a different form to prepare the SDs.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, GBDP was prepared as the solid dispersions with polyethylene glycol 4000 by melting method. Solid dispersion is an efficient technology to improve solubilization and bioavailability of insoluble drugs including G. biloba leaf extract [ 19 ], whereas PEG 4000 is a commonly used carrier matrix for solid dispersion [ 20 , 21 ]. It has been demonstrated that G. biloba extract solid dispersions have higher dissolution and faster dissolution rate than natural extract [ 22 ].…”
Section: Methodsmentioning
confidence: 99%
“…Alteration of the structure is thus, likely to reduce the antimicrobial efficacy. To increase the bioavailability of sc1o without reducing its antimicrobial efficacy, a suitable formulation such as solid dispersions, offers many benefits over conventional drug delivery approaches 18 .…”
Section: Discussionmentioning
confidence: 99%